Urban sustainability and justice just sustainabilities and environmental planning - Castán Broto, Vanesa; Westman, Linda (Just sustainabilities, 2019)
An assessment of sustainability initiatives in over 200 cities offering a practical approach to just sustainability as a framework for urban development